Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T18:43:56+01:00
A)
2*(x+2)-3*(x-1)+8=3x-1
2x+4-3x+3+8=3x-1
2x-3x+3x=-1-8-4
2x=-13|:2
x=-6,5

b)
4x-3*(x=7)-5x=2*(x-1)=9
4x=3x-21-5x+2x-2=9
4x-3x-5x=2x=9+2+21
6x-8x=32
-2x=32|:(-2)
x=-16

c)
½x-7=⅓x-12|*6
3x-42=2x-72
3x-2x=-72+42
x=-30

d)
5x(x-2)-x(5x-2)=-4
5x²-10x-5x²+2x=-4
-8x=-4|:(-8)
x=0,5

e)
x(2-x)+(x+2)x=2*(2-x)+2
2x-x²+x²+2x=4-2x+2
2x=6|:2
x=3

f)
(2x-3)*2x+5x-4x(x-2)+49==4x-1
4x²-6x+5x-4x²-8x+49=-4x-1
4x²-6x+5x-4x²-8x+4x=-1-49
9x-14x=-50
-5x=-50|:(-5)
x=10
2010-03-14T19:39:40+01:00
A)
2(x+2) - 3(x-1) + 8 = 3x - 1
2x + 4 - 3x + 3 + 8 = 3x - 1
2x - 3x + 3x = -1 -8 -4
2x = -13 /:2
x = -6,5

b)
4x - 3(x + 7) -5x + 2(x-1) = 9
4x - 3x - 21 - 5x + 2x - 2 = 9
4x - 3x - 5x - 2x = 9 + 2 + 21
6x - 8x = 32
-2x = 32 /:(-2)
x = -16

c)
0,5x - 7 = 0,2x - 12 /x6
3x - 42 = 2x - 72
3x - 2x = -72 + 42
x = -30

d)
5x(x-2) - x(5x-2) = -4
5x² - 10x - 5x² + 2x = -4
-8x = -4 /:(-8)
x = 0,5

e)
x(2-x) + (x+2) x = 2x(2-x) + 2
2x - x² + x² + 2x = 4 - 2x + 2
2x = 6 /:2
x = 3

f)
(2x-3)2x + 5x -4x(x-2) + 49 = 4x - 1
4x²- 6x + 5x - 4x² - 8x + 49 = 4x - 1
4x² - 6x + 5x -4x² - 8x + 4x = -1 - 49
9x - 14x = -50
-5x = -50 /:(-5)
x = 10